Analysis of the influence of various means of general physical training on the indicators of intracardiac hemodynamics and diastolic heart function in athletes of senior ranks in boxing - Neupokoev, S. N.; Shilko, V. G.; Bredikhina, Yu. P.; Katkov, V. A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to analyze the effect of various means of general physical training on the indices of intracardiac hemodynamics and diastolic function of the heart in senior athletes in boxing.